Pulmonary adverse events following immune checkpoint inhibitors. Issue 5 (16th September 2022) - Spagnolo, Paolo; Chaudhuri, Nazia; Bernardinello, Nicol; Karampitsakos, Theodoros; Sampsonas, Fotios; Tzouvelekis, Argyrios
Abstract : Purpose of review: Immune checkpoint inhibitors (ICIs) have rapidly become a mainstay of cancer treatment. However, immune modulation resulting from checkpoint inhibition can cause inflammation in any organ system, with pneumonitis being one of the most severe immune-related adverse events (irAEs). Here, we review the most recent literature on pulmonary adverse events following ICIs. Recent findings: Several systematic reviews and meta-analyses of data from trials of antiprogrammed death-1 (PD-1; nivolumab, pembrolizumab), anti-PD-ligand-1 (PD-L1; atezolizumab, avelumab, durvalumab) and anticytotoxic T lymphocyte antigen-4 (CTLA-4; ipilimumab or tremelimumab) in patients with advanced cancer have explored the relative risk and incidence of lung toxicity among different tumor types and therapeutic regimens. They have showed that the incidence of all-grade (1–4) and high-grade (3–4) pneumonitis is significantly higher in nonsmall cell lung cancer (NSCLC) compared with other tumor types. In addition, they have demonstrated that immunotherapy, especially monoimmunotherapy, has a significantly lower risk of irAEs compared to immune-chemotherapy. Treatment for lung cancer, preexisting interstitial lung disease, smoking history and male sex appear to increase the risk for ICI-related pneumonitis. Summary: Lung toxicity is an uncommon but potentially severe and even fatal complication of ICIs. Timely recognition is critically important but challenging, particularly in patients with lung cancer wherein drug toxicity can mimic disease progression or recurrence.